2007
DOI: 10.1111/j.1460-9568.2007.05706.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the subthalamic nucleus upon the damage to the dopamine system following lesions of globus pallidus in rats

Abstract: Lesioning or stimulating the subthalamic nucleus (STN) in patients with Parkinson's disease, or in animal models of parkinsonism, alleviates many of the symptoms and so it is tempting to think of the STN as a part of the cause of Parkinson's disease. The globus pallidus (GP) is thought to have a tonic inhibitory action on the STN. An ibotenic acid injection into the GP in rats removes the cells of the GP and, over the following 6 weeks, a progressive loss of dopamine cells (counted stereologically in sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The only conclusion that can be reached is that these delayed changes most likely reflect reactive neurochemical and/or anatomical adjustments that occur in the basal ganglia following the primary insult produced by Mn. This is consistent with the findings that selective injury to the globus pallidus, by as yet an undefined mechanism, can subsequently lead to significant reduction of the number of dopaminergic neurons in the substantia nigra (Wright et al 2004;Wright and Arbuthnott 2007).…”
Section: Symptoms Of Manganism and The Relationship To Parkinsonismsupporting
confidence: 90%
“…The only conclusion that can be reached is that these delayed changes most likely reflect reactive neurochemical and/or anatomical adjustments that occur in the basal ganglia following the primary insult produced by Mn. This is consistent with the findings that selective injury to the globus pallidus, by as yet an undefined mechanism, can subsequently lead to significant reduction of the number of dopaminergic neurons in the substantia nigra (Wright et al 2004;Wright and Arbuthnott 2007).…”
Section: Symptoms Of Manganism and The Relationship To Parkinsonismsupporting
confidence: 90%
“…The threshold-like behavior of SNc cell loss and STN synchrony might be facilitated by the inhibitory drive from GPe to STN as result of the proliferation of GPe-STN synapses (Fan et al, 2012) which also acts as a presymptomatic compensatory mechanism. It was also reported that lesioning of GPe caused progressive SNc cell loss by increasing STN activity (Wright et al, 2002) and lesioning of STN proven to be neuroprotective (Wright and Arbuthnott, 2007).…”
Section: Excitotoxicity Modelmentioning
confidence: 98%
“…Nevertheless, further support for STN‐mediated glutamate excitotoxicity is given by the observation that lesioning the GPe in the rat also leads to some loss of dopaminergic cells in the SNc . This neurodegenerative effect could be prevented by prior lesioning of the STN, suggesting that it was likely mediated by increased STN activity because of loss of GABA‐ergic tone from the GPe . More recently, partial subthalamotomy was shown to improve cell survival following dopaminergic cell transplantation in 6‐OHDA‐lesioned rats, and the neuroprotective effect of subthalamotomy was confirmed in MPTP‐treated monkeys .…”
Section: The Subthalamic Nucleus As a Target To Halt Neurodegeneratiomentioning
confidence: 99%